STRATEGI PENGELOLAAN LINGKUNGAN DALAM MENDUKUNG SEKOLAH ADIWIYATA NASIONAL DI SEKOLAH MENENGAH KEJURUAN (SMK) KEHUTANAN NEGERI PEKANBARU - Desis Tri Yenti; Zulfan Saam; Yusni Ikhwan Siregar (Jurnal Ilmu Lingkungan, 2020)
Adiwiyata’s program was made to created awareness and knowledge in an attempt conservation of the environment. This program expected to every school residents to join school activities toward a healthy environment and avoiding negative environmental impact. This program aims to create a good school condition become a place to study of awareness school residents, so that in the next day school residents be responsible in an effort to save environment and sustainable development. One of school that approved Adiwiyata’s appreciation is Forestry Vocational School Pekanbaru. This research aims to determining ecological management strategies to support national adiwiyata school in Forestry Vocational School Pekanbaru. The method used was interviews, observation and test. To data analysis used SWOT. Environmentalist strategies is to increase participation of interviewer to support environmentally sound policies and to increase the quality of management and utilization of eco-friendly facilities and infrastructure so that it can be reference to give supporting to society or another school by involving the parents of protege and committee .